Maternal responsiveness and toddler body mass index z-score: Prospective analysis of maternal and child mealtime interactions. (1st January 2023) - Hart, C.N.; Phelan, S.; Coffman, D.L.; Jelalian, E.; Ventura, A.K.; Hodges, E.A.; Hawley, N.; Fisher, J.O.; Wing, R.R.
Abstract: Responsive feeding, where parents are guided by children's hunger and satiation cues and provide appropriate structure and support for eating, is believed to promote healthier weight status. However, few studies have assessed prospective associations between observed parental feeding and toddler growth. We characterized toddler growth from 18 to 36 months and, in a subset of families, examined whether observed maternal responsiveness to toddler satiation cues and encouraging prompts to eat at 18 and 24 months were associated with toddler body mass index z-score (BMIz) from 18 to 36 months. Participants included 163 toddlers and their mothers with overweight/obesity who had participated in a lifestyle intervention during pregnancy. Anthropometrics were measured at 18, 24, and 36 months. In a subsample, mealtime interactions were recorded in families' homes at 18 (n = 77) and 24 (n = 75) months. On average, toddler BMIz remained stable from 18 to 36 months with 31.3% (n = 51) categorized with a healthy weight, 56.4% (n = 92) with at risk for overweight and 12.3% (n = 20) with overweight. Fewer maternal prompts to eat at 18 months was associated with both higher probability of having at risk for overweight/overweight ( p < .05), and higher child 36-month BMIz ( p = .002). Higher child weight status at 12 months was also associated with both higher probability of having at risk for overweight/overweight ( p < .05), and higher child 36-month BMIz ( p < .001). Neither 24-month maternal prompts nor 18 or 24 month responsiveness to satiation cues were associated with toddler BMIz. In this diverse sample, weight status was relatively stable from 18 to 36 months. Maternal prompts to eat measured earlier in toddlerhood and prior child weight status were associated with toddler BMIz.